Edukasi dan Simulasi Bekerja Sehat Selamat pada Pekerja Industri Batu Bata di Korong Tanjung Pisang Nagari Sintuk Kabupaten Padang Pariaman - Fitriyani Fitriyani; Mega Utami Basra; Anggela Pradiva Putri; Fauziah Hermawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
In order to achieve success and high work productivity, informal sector businesses, which are growing fast in society, need excellent occupational health support. However, the number of workers in Indonesia is directly proportional to the number of work accidents, which is still high. Based on Social Security Administering Agency (BPJS) data in 2018, work accident cases were 123,000, an increase of 20% compared to 2017. Brick production business is one of the informal industries that found in various regions, including in Korong Tanjung Pisang Nagari Sintuk, Padang Pariaman Regency, West Sumatra. Worker activities risk accidents such as being crushed, falling, burns, and occupational diseases such as respiratory infections, low back pain, dermatitis, nail damage, and work fatigue. The activity method was door-to-door hazard communication on the first day and safe and healthy work education with simulations on the second day. The activity resulted in increased participants' knowledge about workplace hazards and risks and healthy and safe working methods. It was indicated by the increasing number of workers who know healthy and safe working. The pre-test result was that five workers had high knowledge, three had moderate knowledge, and 17 had insufficient knowledge. However, in the post-test result, 18 workers had high knowledge, three had moderate knowledge, and four had low knowledge. In conclusion, this activity is beneficial, providing a solution for a better way of working.